Obsessive-Compulsive Symptoms, Polygenic Risk Score, and Thalamic Development in Children From the Brazilian High-Risk Cohort for Mental Conditions (BHRCS) - Ravagnani Salto, Ana Beatriz; Santoro, Marcos L.; Hoexter, Marcelo Q.; Jackowski, Andrea Parolin; Pan, Pedro M.; Rosário, Maria Conceição; Belangero, Sintia I.; Alvarenga, Pedro Gomes; Doretto, Victoria Fogaça; Fumo, Afonso Mazine Tiago; Batistuzzo, Marcelo C.; Macul Ferreira de Barros, Pedro; et al. (Frontiers in Psychiatry, 2021)
Background: Thalamic volume measures have been linked to obsessive compulsive disorder (OCD) in children and adolescents. However, it is unclear if alterations in thalamic volumes occur before or after symptom onset and if there is a relation to the presence of sub-clinical obsessive-compulsive symptoms (OCS). Here, we explore the relationship between OCS and the rate of thalamic volume change in a cohort of children and youth at high risk to develop a mental disorder. A secondary aim was to determine if there is a relationship between OCS and the individual’s OCD polygenic risk score (OCD-PRS) and between the rate of thalamic volume change and the OCD-PRS. Methods: The sample included 378 children enrolled in the longitudinal Brazilian High-Risk Cohort for Mental Conditions. Participants were assessed for OCS and the symmetrized percent change (SPC) of thalamic volume across two time-points separated by three years, along with the OCD-PRS. Zero-altered negative binomial models were used to analyze the relationship between OCS and thalamic SPC. Multiple linear regressions were used to examine the relationship between thalamic SPC and OCD-PRS. Results: A significant relationship between OCS and the right thalamus SPC (p= 0.042) was found. There was no significant relationship between changes in thalamic volume SPC and OCD-PRS. Conclusions: The findings suggest that changes in the right thalamic volume over the course of three years in children may be associated to emerging OCS. Future studies are needed to confirm these results and further characterize the specific nature of OCS symptoms associated with thalamic volumes.